Endotracheal Administration of Sufentanil and Tetracaine During Awake Fiberoptic Intubation. (January 2016) - Ji, Meng; Tao, Jun; Cheng, Min; Wang, Qingli
Abstract : Combined use of local anesthetics and low-dose opioids enhances the effects of local anesthetics. This study aimed to evaluate the efficacy of combined administration of sufentanil and tetracaine through the cricothyroid membrane during awake nasal intubation using fiberoptic bronchoscopy in patients with difficult airways. Forty patients were divided into 2 groups: group A received endotracheal administration of 25 μg of sufentanil and 2 mL of 1% tetracaine mixture; group B received endotracheal administration of 2 mL 1% tetracaine and routine local anesthetic sprays followed by slow intravenous injection of 25 μg of sufentanil. The results showed that endotracheal intubation was safely completed in all patients and vital signs including blood pressure, heart rate, and pulse oxygen saturation were not significantly different between groups A and B. However, time required for local anesthesia to take effect, time required to complete intubation, cough reflex, patient tolerance during intubation, and hemodynamic indices were significantly better in group A than in group B. In conclusion, our results suggest that endotracheal administration of sufentanil combined with tetracaine is safe, effective, and feasible in the context of awake nasal intubation using fiberoptic bronchoscopy.